(3YLGdI GdEedGA GdeJjSQI ef GdJPfjH Ydi eG hbY ddMGaX GdefPQi ef Gdhge hZjQg aj cJGHg GdJQZjH hGdJQgjHs - (3CHh ESMGb HQgGf GdOjf EHQGgje Hf eMeO GdfGLi GdOeTbj,J (B900 (3g` s ((3EHQGgje Hf eMeO Hf EHQGgje GdTgjQ HGHf GdUGQe s)
(3ChdgG (B:s
(3bGd NGOe GdSfI GdedbH HGdfGLi CeG HYO MeO Gddg GdYdje GdPi dG jZQH Yf Ydeg TF hdG jZjH agPg fcJ bdjdI dcfgG egeI LdjdI s
(3BNQgG (B:s
(3hCSGd Gddg GdYXje GdcQje CYXe ef SFd hCcQe ef CLGH hdg GdMeO GdefI hHg GdJhajb s
(3GdfSNI HgG MhGTs
(3HBNQgG UhQI ELGRI HNW GdeDda efbhdI ef GdCUd GdefJSN efgs
(3hHChdgG Jedc SfI (B954s
(3aQZ GdeUfa ef JUfja GdcJGH SfI (B875 s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJaSjQ hYdhe GdbQBfs